Productivity improvement framework for South African construction SMEs - Oluseyi Adebowale; Justus Agumba (Journal of Construction Project Management and Innovation)
Contractors’ productivity holds strategic importance for both long-term micro and macroeconomic performance. A significant number of small and medium-sized enterprises (SMEs) in the construction sector in South Africa are characterised by poor performance, which can be attributed, in part, to low productivity rates. This scenario contributes to a pessimistic outlook for the South African construction industry and undermines its potential for job creation. This study aims to investigate the primary obstacles that hinder productivity within construction SMEs and proposes an improvement framework. The study employed a qualitative research approach, collecting data from registered SMEs in South Africa through semi-structured interviews. Qualitative content analysis was applied to analyse the research data. The key factors identified as undermining SMEs’ productivity include challenges related to workers' skillsets, directors' competencies, government interference, and workers’ remuneration. The implications of this research are valuable for SMEs, offering insights to expedite project delivery and thereby mitigating the risk of construction business failure. Previous studies have often focused on the overall performance of construction SMEs, with limited attention to their productivity. Moreover, productivity-focused studies tend to lack a strong SME-centered approach. This research bridges these gaps and introduces interventions that have the potential to enhance productivity in small and medium-sized construction organisations.